Epilepsy in Loeys-Dietz Syndrome: The Rare Concurrence of a Connective Tissue and Neuronal Migration Disorder - Fatima Farid Mir; Mohammad Ashraf (Dubai Medical Journal)
We present a 7-year-old girl who presented to our emergency department in active status epilepticus. Seizures responded to standard antiepileptic medications; however, baseline work-up for seizure etiology remained unremarkable. Her new-onset seizures were further investigated via EEG and MRI brain, which revealed focal epileptiform discharges and periventricular nodular heterotopia, respectively. Concurrently, the clinical evaluation revealed extensive marfanoid features, and a personal history of eczema and asthma. Her family history was pertinent for aortic valve disease, asthma, and tall stature. Given the peculiar skeletal features, allergic propensities and coexistent weighty family history, a molecular genetic panel analysis for Marfan Syndrome and Loeys-Dietz Syndrome (LDS) were sought. Genetic testing revealed an underlying heterozygous variant in the TGFBR-1 gene; thereby confirming the presence of LDS. The child had responded well to single antiepileptic agent therapy and was discharged in good condition with regular outpatient cardiac and neurology follow-up. This is a unique case reported of a child with genetically diagnosed LDS concurring with an underlying neuronal migration disorder, manifesting in an acute, severe, and lifethreatening fashion.